Bioethanol production from coconuts and cactus pretreated by autohydrolysis - Gonçalves, Fabiano Avelino (2015)
The use of coconut fiber mature, green coconut shell, mature coconut shell and cactus is an important alternative as substrates for bioethanol production, since these lignocellulosic materials (LCMs) are abundant in Brazil, mainly in the Northeast Region. The first objective of this work was to evaluate the autohydrolysis pretreatment (AP) on these LCMs and the susceptibility of the treated materials to enzymatic hydrolysis (EH). The second part of the work deals with the application of semi-simultaneous saccharification and fermentation (SSSF) and simultaneous saccharification and fermentation (SSF) using Zymomonas mobilis, Pichia stipitis, Saccharomyces cerevisiae and as substrate the green coconut shell (selected according to the results obtained in the first part of the work). The LCMs after AP using the highest severity factor (4.64) showed changes in the chemical composition in comparison to the untreated LCMs: between the LCMs the cellulose increase was 48.55%, the hemicellulose decrease was 76.77% and an increase of 62.26% was observed for lignin. The green coconut shell was characterized by SEM, X-ray and FTIR after AP and its EH conversion into glucose was 92.52%. The best results on ethanol yield (90.09%) and ethanol productivity (0.21 g/(L h)) from green coconut shell were obtained by S. cerevisiae using SSSF. Overall, an efficient process for the bioethanol production from green coconut shell was developed.